The A Hybrid Weighted Ensemble classifier model for medical databases - P R Sudha Rani , Dr. K R Ramya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Extreme learning approaches are now widely used to identify and diagnose medical conditions for large databases. Ensemble classifier was a key study model for extreme learning machines for real-time applications due to its great performance and processing speed. Due to the static weight selection of the output layer hidden, standard extreme learning methods are unable to estimate the error rate. This research introduces a novel weighted extreme learning machine (WELM) for medical condition prediction. The basic goal of the weighted extreme learner is to define high-dimensional data for illness prediction. Typically, the proposed ensemble model is created and deployed to improve cancer prediction using high-dimensional data. Using several ensemble learning models such as random forest, neural networks, ACO+NN, and PSO+NN, we evaluated the performance of the WELM model suggested in this paper. Test outcomes are examined in a variety of medical datasets, including liver, diabetes, ovarian, and DLBCL-Stanford. The WELM presented is highly computationally efficient in terms of true positive rate, error rate, and accuracy, according to the results.